EFEKTIVITAS KERJA KADER POSYANDU DALAM MENINGKATKAN KESEHATAN IBU PADA PROGRAM KB DI KECAMATAN KAMPA KABUPATEN KAMPAR - Syahriani Huduriah Hutasuhut; Jaspar Jas; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the level of effectiveness of posyandu cadre work in improving maternal health in family planning program in Kampar district of Kampar regency. The formulation of the problem of this research is to know the level of effectiveness of posyandu cadre work in improving maternal health in family planning program in kampa sub district of Kampar regency. The population in this study as many as 50 people. So the researchers used the sample saturated so that all the population sampled as many as 50 people, and 20 people for a sample test questionnaire at Posyandu District Tambang Kampar regency. The type of this research is descriptive with quantitative approach. Instrument data collection is a questionnaire with 42 statements and after the test remaining 38 valid statements to be used as research instruments. Data analysis through quantitative descriptive analysis. The findings of this study indicate that the effectiveness of posyandu cadre work in improving maternal health in family planning program in Kampar sub-district of Kampar regency is the highest with extension 85%.Keywords: Work Effectiveness, Posyandu cadres.